Biomass-based hard carbon negative electrode material and preparation method thereof and sodium ion battery

CN119591083BActive Publication Date: 2026-10-16GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411789342.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2026-10-16
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

但相对聚合物和化石燃料而言,比容量、动力学性能、压实密度依旧是生物质硬炭的短板

Benefits of technology

[0005] The purpose of this invention is to provide a biomass-based hard carbon anode material, its preparation method, and its application in sodium-ion batteries. The biomass-based hard carbon anode material of this invention has suitable compaction density and specific surface area, and its use in sodium-ion batteries can effectively improve their specific capacity, initial coulombic efficiency, and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591083B_ABST
    Figure CN119591083B_ABST
Patent Text Reader

Abstract

The application provides a biomass-based hard carbon negative material and a preparation method thereof and a sodium ion battery, and relates to the technical field of sodium ion battery negative materials. The preparation method of the biomass-based hard carbon negative material comprises the following steps: S1, coarsely crushing and pre-carbonizing a biomass hard carbon precursor to obtain a pre-carbonized material; S2, performing crushing, acid washing, water washing and drying on the pre-carbonized material to obtain a purified treatment material; S3, adding a silane coupling agent into water to perform first mixing and stirring to obtain a first solution, adding the purified treatment material into the first solution to perform second mixing and stirring to obtain a second solution, adding a phosphorus-containing dopant into the second solution to perform third mixing and stirring, and then drying to obtain a first precursor; and S4, carbonizing and screening the first precursor. The biomass-based hard carbon negative material prepared by the application has a suitable compaction density and specific surface area, and can effectively improve the specific capacity, the first coulomb efficiency and the rate performance of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery anode material technology, and particularly to biomass-based hard carbon anode materials, their preparation methods, and sodium-ion batteries. Background Technology

[0002] Lithium-ion batteries, as a common type of rechargeable battery, have been widely used in 3C products, power batteries, and energy storage. However, with the continuous expansion of production, the drawbacks of uneven lithium resource distribution, insufficient reserves, and high costs have become increasingly apparent. The huge supply-demand imbalance and repeated price fluctuations have become a dark cloud hanging over the entire industry chain. Meanwhile, with continuous breakthroughs in technological barriers, especially the continuous improvement of hard carbon anodes with excellent sodium storage performance, sodium-ion batteries have returned to the public eye. Their significant cost advantage makes them a highly sought-after alternative to lithium-ion batteries.

[0003] Sodium-ion batteries, like lithium-ion batteries, are "rocking chair batteries," where charge transfer occurs through the extraction and insertion of sodium or lithium ions at the positive and negative electrodes during charging and discharging. Besides their cost advantage, sodium-ion batteries offer high safety and excellent high and low temperature performance, but their energy density and cycle life still lag behind lithium-ion batteries. Currently, the precursors for hard carbon anode materials in sodium-ion batteries mainly include biomass, synthetic polymers, and fossil fuels. Among these, biomass-based hard carbon materials are considered highly promising cutting-edge anode materials due to their unique natural microstructure, high purity, functional diversity, and easily tunable structure. However, compared to polymers and fossil fuels, specific capacity, kinetic performance, and compaction density remain weaknesses for biomass hard carbon.

[0004] Therefore, there is an urgent need for a biomass-based hard carbon anode material and its preparation method, along with sodium-ion batteries, to address the shortcomings of existing technologies. Summary of the Invention

[0005] The purpose of this invention is to provide a biomass-based hard carbon anode material, its preparation method, and its application in sodium-ion batteries. The biomass-based hard carbon anode material of this invention has suitable compaction density and specific surface area, and its use in sodium-ion batteries can effectively improve their specific capacity, initial coulombic efficiency, and rate performance.

[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a biomass-based hard carbon anode material, comprising:

[0007] S1 involves coarsely crushing and pre-carbonizing the biomass hard carbon precursor to obtain pre-carbonized material.

[0008] S2 involves crushing, acid washing, water washing, and drying the pre-carbonized material to obtain purified material;

[0009] S3 is mixed with water and a silane coupling agent once to obtain a first solution. Purified material is added to the first solution and mixed and stirred a second time to obtain a second solution. A phosphorus-containing dopant is added to the second solution and mixed and stirred a third time before drying to obtain the first precursor.

[0010] S4 carbonizes and sieves the first precursor.

[0011] Compared with existing technologies, this invention first coarsely crushes and pre-carbonizes the biomass hard carbon precursor to obtain pre-carbonized material, effectively removing moisture and volatile organic compounds from the biomass, facilitating subsequent purification, doping, and carbonization. Acid washing of the pre-carbonized material effectively removes acid-soluble impurities, improving its purity. Simultaneously, the acid washing process introduces oxygen-containing functional groups onto the material's surface, benefiting subsequent coating and modification of the purified material by silane coupling agents and phosphorus-containing dopants. A silane coupling agent is added to water to form a first solution. During stirring, the silane coupling agent hydrolyzes in water to form silanol bonds. The purified material is then added to the first solution and stirred to form a second solution. During stirring, the formed silanol bonds can bind with the purified material. The oxygen-containing functional groups on the surface of the raw material form strong covalent bonds, thereby uniformly and firmly loading the silane coupling agent onto the surface of the purified raw material. Finally, a phosphorus-containing dopant is added to the second solution to react with the organic functional groups of the silane coupling agent, forming stable chemical bonds. This achieves a tight bond and uniform coating between the purified raw material, the silane coupling agent, and the phosphorus-containing dopant. The resulting first precursor is then carbonized. During carbonization, the silane coupling agent pyrolyzes into silane and eventually decomposes into elemental silicon, increasing the specific capacity of the biomass-based hard carbon anode material. The phosphorus-containing dopant, after carbonization and pyrolysis, fills the pores on the material surface. Simultaneously, the introduction of phosphorus effectively improves the initial coulombic efficiency and rate performance of the anode material of this invention. Therefore, the biomass-based hard carbon anode material prepared by the method of this invention possesses suitable compaction density and specific surface area, and can effectively improve the initial coulombic efficiency and rate performance in sodium-ion batteries.

[0012] In some implementation schemes, the biomass hard char precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch and glucose, and the particle size Dv50 of the coarsely crushed material is 1 mm to 8 mm.

[0013] In some implementation schemes, pre-carbonization is carried out in an inert atmosphere at a temperature of 400°C to 700°C for a holding time of 0.5 h to 10 h.

[0014] In some embodiments, the pulverization method includes at least one of air jet milling, roller milling and mechanical milling, the particle size Dv 50 of the pulverized material is 4μm to 10μm, the drying temperature is 80℃ to 200℃, and the drying time is 2h to 24h.

[0015] In some embodiments, acid washing includes placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100 rpm to 200 rpm for 2 h to 24 h. The acid solution is selected from at least one of hydrochloric acid, nitric acid and hydrofluoric acid. The mass ratio of the acid solution to the pre-carbonized material is 0.2 to 5:1, and the pH of the acid solution is 1 to 3. Water washing includes repeatedly washing the acid-washed pre-carbonized material with water until the pH of the filtrate is greater than 2.

[0016] In some embodiments, the silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902 and WD-50, and the phosphorus dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate and dimethyl phosphate. The mass ratio of the silane coupling agent, the purified material and the phosphorus dopant is 0.01-0.1:1-10:0.1-1.

[0017] In some implementations, the mixing speed for the first mixing step is 200 rpm to 300 rpm, and the mixing time for the first mixing step is 0.5 h to 5 h; the mixing speed for the second mixing step is 300 rpm to 500 rpm, and the mixing time for the second mixing step is 0.5 h to 5 h; the mixing speed for the third mixing step is 150 rpm to 300 rpm, and the mixing time for the third mixing step is 1 h to 10 h; the drying temperature is 50 °C to 200 °C, and the drying time is 12 h to 48 h.

[0018] In some implementation schemes, carbonization is carried out in an inert atmosphere, the heating rate of carbonization is 1℃ / min to 10℃ / min, the carbonization temperature is 1000℃ to 1600℃, the holding time is 0.5h to 10h, and the sieve mesh used for screening is 200 mesh to 400 mesh.

[0019] The second aspect of the present invention provides a biomass-based hard carbon anode material, which is prepared by the aforementioned method for preparing biomass-based hard carbon anode materials.

[0020] A third aspect of the present invention provides a sodium-ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the aforementioned biomass-based hard carbon negative electrode material. Attached Figure Description

[0021] Figure 1 This is a SEM image of the biomass-based hard carbon anode material prepared in Example 1 of the present invention. Detailed Implementation

[0022] This invention provides a sodium-ion battery, comprising a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the biomass-based hard carbon negative electrode material of this invention. The preparation of the biomass-based hard carbon negative electrode material of this invention includes:

[0023] S1 involves coarsely crushing and pre-carbonizing the biomass hard carbon precursor to obtain pre-carbonized material.

[0024] S2 involves crushing, acid washing, water washing, and drying the pre-carbonized material to obtain purified material;

[0025] S3 is mixed with water and a silane coupling agent once to obtain a first solution. Purified material is added to the first solution and mixed and stirred a second time to obtain a second solution. A phosphorus-containing dopant is added to the second solution and mixed and stirred a third time before drying to obtain the first precursor.

[0026] S4 carbonizes and sieves the first precursor.

[0027] In S1, the biomass hard char precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch, and glucose. In some technical solutions, the biomass hard char precursor is selected from coconut shell. In some technical solutions, the biomass hard char precursor is selected from both coconut shell and bamboo. In some technical solutions, the biomass hard char precursor is selected from lignin. In some technical solutions, the biomass hard char precursor is selected from microcrystalline cellulose. In some technical solutions, the biomass hard char precursor is selected from starch. In some technical solutions, the biomass hard char precursor is selected from glucose. Using biomass-based hard char precursors is low-cost and has advantages such as being renewable, abundant in sources, inexpensive, and environmentally friendly.

[0028] The particle size Dv 50 of the biomass hard char precursor after coarse crushing is 1 mm to 8 mm. For example, the particle size Dv 50 of the coarsely crushed material can be, but is not limited to, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, or 8 mm. Pre-carbonization is carried out in an inert atmosphere. The inert atmosphere is selected from at least one of nitrogen, helium, and argon. The pre-carbonization temperature is 400℃ to 700℃. In some technical solutions, the pre-carbonization temperature is 420℃ to 685℃, and in some technical solutions, the pre-carbonization temperature is 465℃ to 595℃. For example, the pre-carbonization temperature can be, but is not limited to, 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃, 540℃, 560℃, 580℃, 600℃, 620℃, 640℃, 660℃, 680℃, or 700℃. The pre-carbonization holding time is 0.5h to 10h. In some technical solutions, the pre-carbonization holding time is 4h to 10h, in others it is 5h to 8h, and in still others it is 6h to 7h. As examples, the pre-carbonization holding time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, or 10h. Pre-carbonizing the biomass-based hard carbon precursor at 400℃ to 700℃ can effectively remove moisture and volatile organic compounds present in the biomass, improve the energy density and bulk density of the biomass, and avoid the rapid volatilization of moisture and volatile organic compounds during direct carbonization at high temperatures, which would negatively impact the carbonization effect.

[0029] In S2, the pulverization method includes at least one of air jet milling, roller milling, and mechanical milling. The particle size Dv 50 of the pulverized material is 4μm to 10μm. As an example, the particle size Dv 50 of the pulverized material can be, but is not limited to, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm. The pulverized material is demagnetized to reduce the content of magnetic materials in the material, thereby reducing the impact of magnetic material content on the electrochemical performance of subsequent biomass-based hard carbon anode materials. Demagnetization can be carried out in a demagnetizer.

[0030] The drying temperature ranges from 80℃ to 200℃. In some technical solutions, the drying temperature is 86℃ to 195℃; in others, it is 90℃ to 180℃; and in still others, it is 100℃. For example, the drying temperature can be, but is not limited to, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, or 200℃. The drying time ranges from 2 hours to 24 hours. In some technical solutions, the drying time is 4 hours to 24 hours; and in still others, it is 6 hours to 20 hours. As an example, the drying time can be, but is not limited to, 2h, 4h, 6h, 8h, 10h, 11h, 12h, 14h, 16h, 18h, 20h, 22h, or 24h.

[0031] Pickling involves placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100 rpm to 200 rpm for 2 h to 24 h. For example, the stirring rate can be, but is not limited to, 100 rpm, 110 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm, 160 rpm, 170 rpm, 180 rpm, 190 rpm, or 200 rpm. The stirring and washing time can be, but is not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 12 h, 14 h, 16 h, 18 h, 19 h, 20 h, 22 h, or 24 h. The acid solution is selected from at least one of hydrochloric acid, nitric acid, and hydrofluoric acid. In some technical solutions, the acid solution is hydrochloric acid; in others, it is nitric acid; and in still others, it is hydrofluoric acid. The mass ratio of acid solution to pre-carbonized material is 0.2–5:1. In some technical solutions, the mass ratio is 1–5:1, and in others, it is 2–5:1. For example, the mass ratio of acid solution to pre-carbonized material can be, but is not limited to, 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1. The pH of the acid solution is 1–3. For example, the pH of the acid solution can be, but is not limited to, 1, 2, or 3. During the acid washing process, in addition to effectively removing impurities present in the pre-oxidized material, it can also be oxidized to introduce oxygen-containing functional groups. Water washing includes repeatedly washing the acid-washed pre-carbonized material until the pH of the filtrate is greater than 2. For example, the pH of the filtrate after water washing can be, but is not limited to, 2.5, 3, 4, 5, 6, or 7.

[0032] In S3, the silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902, and WD-50, and the phosphorus-containing dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate, and dimethyl phosphate. The mass ratio of silane coupling agent, purified material, and phosphorus-containing dopant is 0.01–0.1:1–10:0.1–1. In some technical solutions, the mass ratio of silane coupling agent, purified material, and phosphorus-containing dopant is 0.3–4:1–8:1. As an example, the mass ratio of silane coupling agent, purified material, and phosphorus-containing dopant can be, but is not limited to, 0.01:1:1, 0.05:1:1, 0.1:1:1, 0.01:2:1, 0.05:2:1, 0.1:2:1, 0.01:4:1, 0.05:4:1, 0.1:4:1, 0.01:6:1, 0.05:6:1, 0.1:6:1, or 0.01:8:1. 0.05:8:1, 0.1:8:1, 0.01:10:1, 0.05:10:1, 0.1:10:1, 0.01:1:0.5, 0.05:1:0.5, 0.1:1:0.5, 0.01:2:0.5, 0.05:2:0.5, 0.1:2:0.5, 0.01:4:0.5, 0.05:4:0.5, 0.1:4:0.5, 0.0 1:6:0.5, 0.05:6:0.5, 0.1:6:0.5, 0.01:8:0.5, 0.05:8:0.5, 0.1:8:0.5, 0.01:10:0.5, 0.05:10:0.5, 0.1:10:0.5, 0.01:1:0.2, 0.05:1:0.2, 0.1:1:0.2, 0.01:2:0.2, 0.05:2 :0.2, 0.1:2:0.2, 0.01:4:0.2, 0.05:4:0.2, 0.1:4:0.2, 0.01:6:0.2, 0.05:6:0.2, 0.1:6:0.2, 0.01:8:0.2, 0.05:8:0.2, 0.1:8:0.2, 0.01:10:0.2, 0.05:10:0.2, 0.1:10:0.2. This invention first dissolves a silane coupling agent in water to form a first solution. The silane coupling agent can form silanol bonds in water. Then, the purified material obtained after acid washing, water washing and drying is placed in the first solution and mixed and stirred to form a second solution. During the mixing and stirring process, the oxygen-containing functional groups on the surface of the purified material can react with the silanol bonds to form a linking bond with strong bonding effect, thereby making the silane coupling agent uniformly loaded on the surface of the purified material. Then, a phosphorus-containing dopant is added to the second solution and mixed and stirred. The phosphorus-containing dopant bonds with the silane coupling agent to form a tightly connected purified material-silane coupling agent-phosphorus-containing dopant structure, which is the first precursor.

[0033] The mixing speed for a single mixing step is 200 rpm to 300 rpm. For example, the mixing speed for a single mixing step can be, but is not limited to, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, or 300 rpm. The mixing time for a single mixing step is 0.5 h to 5 h. For example, the mixing time for a single mixing step can be, but is not limited to, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, or 5 h. The mixing speed for a two-stage mixing step is 300 rpm to 500 rpm. For example, the mixing speed for a two-stage mixing step can be, but is not limited to, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm, or 500 rpm. The mixing time for secondary mixing is 0.5h to 5h. For example, the mixing time for secondary mixing can be, but is not limited to, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, or 5h. The mixing rate for tertiary mixing is 150rpm to 300rpm, and the mixing time for tertiary mixing is 2h to 10h. For example, the mixing rate for tertiary mixing can be, but is not limited to, 150rpm, 170rpm, 200rpm, 220rpm, 250rpm, 280rpm, or 300rpm. The mixing time for tertiary mixing can be, but is not limited to, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, or 10h. The drying temperature is 50℃ to 200℃. For example, the drying temperature can be, but is not limited to, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 82℃, 84℃, 86℃, 88℃, 90℃, 92℃, 94℃, 96℃, 98℃, 100℃, 120℃, 140℃, 160℃, 180℃, or 200℃. The drying time is 12h to 48h. For example, the drying time can be, but is not limited to, 24h to 48h, and can be, but is not limited to, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, or 48h.

[0034] In step S4, carbonization is carried out in an inert atmosphere, selected from at least one of nitrogen, argon, and helium. The heating rate of carbonization is 1℃ / min to 10℃ / min; in some technical embodiments, the heating rate is 2℃ / min to 8℃ / min; in some technical embodiments, the heating rate is 3℃ / min to 7℃ / min; and in some technical embodiments, the heating rate is 5℃ / min. As an example, the heating rate of carbonization can be, but is not limited to, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min. The carbonization temperature is 1000℃ to 1600℃; in some technical embodiments, the carbonization temperature is 1100℃ to 1400℃; and in some technical embodiments, the carbonization temperature is 1180℃ to 1360℃. As an example, the carbonization temperature can be, but is not limited to, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, and 1600℃. The carbonization holding time is 0.5h to 10h; in some technical solutions, it is 3h to 8h; in others, it is 3h to 6h. As an example, the carbonization holding time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h. The sieve mesh size used for screening is 200 mesh to 400 mesh; in some technical solutions, it is 325 mesh to 400 mesh. This is just an example. The mesh size of the sieve used for screening can be, but is not limited to, 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh, 270 mesh, 280 mesh, 290 mesh, 300 mesh, 315 mesh, 325 mesh, 335 mesh, 345 mesh, 355 mesh, 365 mesh, 375 mesh, 385 mesh, 395 mesh, or 400 mesh.

[0035] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.

[0036] Example 1

[0037] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0038] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0039] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0040] S3 was prepared by adding 1g KH-550 to 100g deionized water and stirring at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h to obtain the second solution. 10g of triethyl phosphate was added to the second solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0041] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0042] Figure 1 The SEM image of the biomass-based hard carbon anode material prepared in this embodiment is shown.

[0043] Example 2

[0044] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0045] S1. 200g of moso bamboo is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0046] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0047] S3 was prepared by adding 1g KH-550 to 100g deionized water and stirring at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h to obtain the second solution. 18g of triethyl phosphate was added to the second solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0048] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0049] Example 3

[0050] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0051] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0052] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, the material was filtered under positive pressure to obtain the acid-washed material. The acid-washed material was repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0053] S3 was prepared by adding 1g KH-550 to 100g deionized water and stirring at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h to obtain the second solution. 10g of dimethyl phosphate was added to the second solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0054] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0055] Example 4

[0056] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0057] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0058] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0059] S3 was prepared by adding 0.6g KH-550 to 100g deionized water and stirring at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h to obtain the second solution. 10g of triethyl phosphate was added to the second solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0060] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0061] Example 5

[0062] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0063] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0064] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0065] S3 was prepared by adding 1g KH-550 to 100g deionized water and stirring at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h to obtain the second solution. 15g of triethyl phosphate was added to the second solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0066] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0067] Example 6

[0068] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0069] S1. 500g of moso bamboo is coarsely crushed to Dv 50 of 7mm, then placed in a tube furnace and pre-carbonized at 480℃ for 6h in a nitrogen atmosphere to obtain pre-carbonized material.

[0070] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 4μm. 150g of the pulverized pre-carbonized material was placed in 150g of hydrofluoric acid solution with a pH of 2. After stirring and washing at a stirring rate of 180rpm for 7h, it was filtered under positive pressure. The acid-washed pre-carbonized material was repeatedly washed with water until the pH of the filtrate was 6. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0071] S3 was prepared by adding 1g of A-187 to 100g of deionized water and stirring at 245rpm for 2h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 365rpm for 3h to obtain the second solution. 22g of triethyl phosphate was added to the second solution and stirred at 250rpm for 3h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0072] S4 places the first precursor in an atmosphere furnace and heats it to 1200℃ under a nitrogen atmosphere at a heating rate of 5℃ / min, and holds it for 6 hours. After cooling to room temperature, it is passed through a 285-mesh sieve to obtain biomass-based hard carbon anode material.

[0073] Comparative Example 1

[0074] This comparative example illustrates a method for preparing a biomass-based hard carbon anode material, including:

[0075] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0076] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0077] S3 placed the purified material in an atmosphere furnace and heated it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and held it for 5 hours. After cooling to room temperature, it was passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0078] Comparative Example 2

[0079] This comparative example illustrates a method for preparing a biomass-based hard carbon anode material, including:

[0080] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0081] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0082] S3 was prepared by adding 100g of purified material to 100g of deionized water and stirring at 300rpm for 1h to obtain the first solution. 10g of triethyl phosphate was added to the first solution and stirred at 300rpm for 2h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0083] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0084] Comparative Example 3

[0085] This embodiment describes a method for preparing a biomass-based hard carbon anode material, including:

[0086] S1. 200g of coconut shell is coarsely crushed to Dv 50 of 5mm, then placed in a tube furnace and pre-carbonized at 550℃ for 4h in an argon atmosphere to obtain pre-carbonized material.

[0087] S2 The pre-carbonized material was pulverized by an air jet mill to a Dv 50 of 5μm. 150g of the pulverized pre-carbonized material was placed in 300g of hydrochloric acid solution with a pH of 3. After stirring and washing at a stirring rate of 150rpm for 8h, it was filtered under positive pressure. The acid-washed pre-carbonized material was then repeatedly washed with water until the pH of the filtrate was 5.5. Finally, it was dried in an oven at 100℃ to obtain the purified material.

[0088] S3 was added to 100g of deionized water and 1g of KH-550 was added and stirred at 200rpm for 1h to obtain the first solution. 100g of purified material was added to the first solution and stirred at 300rpm for 1h. The reaction solution was then dried in an oven at 100℃ to obtain the first precursor.

[0089] S4 places the first precursor in an atmosphere furnace and heats it to 1300℃ under an argon atmosphere at a heating rate of 2℃ / min, and holds it at that temperature for 5 hours. After cooling to room temperature, it is passed through a 325-mesh sieve to obtain biomass-based hard carbon anode material.

[0090] Using the biomass-based hard carbon anode materials prepared in Examples 1-6 and Comparative Examples 1-3 as the anode materials, metallic sodium as the cathode material, glass fiber as the separator, and 1 mol / L NaClO4 (PC + 5% FEC) as the electrolyte, coin cells were assembled. Charge-discharge tests were conducted at a current density of 0.1C within the voltage range of 2.0-4.0V, followed by rate performance tests at a current density of 1C. The test results are shown in Table 1.

[0091] The specific surface area was obtained from the nitrogen adsorption / desorption isotherm of the material using a Micromeritics ASAP 2460 analyzer, and its specific surface area was calculated using the BET method.

[0092] The compaction density was determined using a UTM7305 battery powder compaction density tester.

[0093] Table 1 Performance test results of Examples 1-6 and Comparative Examples 1-3

[0094]

[0095] As can be seen from the test results in Table 1, specifically in Examples 1-6 and Comparative Examples 1-3, the biomass-based hard carbon anode material prepared by the method of the present invention has more suitable compaction density and specific surface area, and its comprehensive performance in terms of specific capacity, initial coulombic efficiency and rate capability is more superior.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing biomass-based hard carbon anode material, characterized in that, include: S1 The biomass hard carbon precursor is coarsely crushed and pre-carbonized to obtain pre-carbonized material. The pre-carbonization temperature is 400 ℃~700 ℃ and the holding time is 0.5 h~10 h. S2 involves pulverizing, acid washing, water washing, and drying the pre-carbonized material to obtain a purified material; S3 is prepared by adding a silane coupling agent to water and mixing and stirring once to obtain a first solution. The purified material is then added to the first solution and mixed and stirred a second time to obtain a second solution. A phosphorus-containing dopant is added to the second solution and mixed and stirred a third time, followed by drying to obtain a first precursor. The stirring rate for the first mixing is 200 rpm to 300 rpm, and the stirring time for the first mixing is 0.5 h to 5 h. The stirring rate for the second mixing is 300 rpm to 500 rpm, and the stirring time for the second mixing is 0.5 h to 5 h. The stirring rate for the third mixing is 150 rpm to 300 rpm, and the stirring time for the third mixing is 1 h to 10 h. The phosphorus-containing dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate, and dimethyl phosphate. S4 carbonizes and sieves the first precursor.

2. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The biomass hard char precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch and glucose, and the particle size Dv 50 of the coarsely crushed material is 1 mm to 8 mm.

3. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The pre-carbonization is carried out in an inert atmosphere.

4. The method for preparing the biomass-based hard carbon anode material according to claim 1, characterized in that, The pulverization method includes at least one of air jet milling, roller milling and mechanical milling, the particle size Dv 50 of the pulverized material is 4 μm to 10 μm, the drying temperature is 80 ℃ to 200 ℃, and the drying time is 2 h to 24 h.

5. The method for preparing the biomass-based hard carbon anode material according to claim 1, characterized in that, The acid washing includes placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100 rpm to 200 rpm for 2 h to 24 h. The acid solution is selected from at least one of hydrochloric acid, nitric acid, and hydrofluoric acid. The mass ratio of the acid solution to the pre-carbonized material is 0.2 to 5:1, and the pH of the acid solution is 1 to 3. The water washing includes repeatedly washing the acid-washed pre-carbonized material with water until the pH of the filtrate is greater than 2.

6. The method for preparing the biomass-based hard carbon anode material according to claim 1, characterized in that... The drying temperature is 50 ℃ to 200 ℃, and the drying time is 12 h to 48 h.

7. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902 and WD-50, and the mass ratio of the silane coupling agent, the purified material and the phosphorus dopant is 0.01~0.1:1~10:0.1~1.

8. The method for preparing the biomass-based hard carbon anode material according to claim 1, characterized in that, The carbonization is carried out in an inert atmosphere, the heating rate of the carbonization is 1 ℃ / min to 10 ℃ / min, the carbonization temperature is 1000 ℃ to 1600 ℃, the holding time is 0.5 h to 10 h, and the sieve used for screening is 200 mesh to 400 mesh.

9. A biomass-based hard carbon anode material, characterized in that, It was prepared using the preparation method of biomass-based hard carbon anode material according to any one of claims 1 to 8.

10. A sodium-ion battery, comprising a positive electrode material, a negative electrode material, and an electrolyte, characterized in that, The negative electrode material is the biomass-based hard carbon negative electrode material as described in claim 9.

Citation Information

Patent Citations

  • Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN113381016A

  • High-capacity hard carbon fast-charging negative electrode material as well as preparation method and application thereof

    CN114695894A

  • Biomass-based hard carbon / alloy anode composite material as well as preparation method and application thereof

    CN117691073A